Complete genome sequence of Rhodospirillum rubrum type strain (S1T). Issue 3 (May 2011) - Munk, A.; Copeland, Alex; Lucas, Susan; Lapidus, Alla; Glavina Del Rio, Tijana; Barry, Kerrie; Detter, John; Hammon, Nancy; Israni, Sanjay; Pitluck, Sam; Brettin, Thomas; Bruce, David; et al.
Abstract Rhodospirillum rubrum (Esmarch 1887) Molisch 1907 is the type species of the genusRhodospirillum, which is the type genus of the familyRhodospirillaceae in the classAlphaproteobacteria . The species is of special interest because it is an anoxygenic phototroph that produces extracellular elemental sulfur (instead of oxygen) while harvesting light. It contains one of the most simple photosynthetic systems currently known, lacking light harvesting complex 2. Strain S1T can grow on carbon monoxide as sole energy source. With currently over 1, 750 PubMed entries, R. rubrum is one of the most intensively studied microbial species, in particular for physiological and genetic studies. Next toR. centenum strain SW, the genome sequence of strain S1T is only the second genome of a member of the genusRhodospirillum to be published, but the first type strain genome from the genus. The 4, 352, 825 bp long chromosome and 53, 732 bp plasmid with a total of 3, 850 protein-coding and 83 RNA genes were sequenced as part of the DOE Joint Genome Institute Program DOEM 2002.